High Performance Computing on Vector Systems 2008 - Roller, Sabine; Benkert, Katharina; Galle, Martin; Bez, Wolfgang; Kobayashi, Hiroaki; Hirayama, Toshio (Springer Berlin Heidelberg : Imprint: Springer, 2009)
This book presents the state of the art in high-performance computing and simulation on modern supercomputer architectures. It covers trends in hardware and software development in general and specifically the future of vector-based systems and heterogeneous architectures. The application contributions cover computational fluid dynamics, fluid-structure interaction, physics, chemistry, astrophysics, and climate research. Innovative fields like coupled multi-physics or multi-scale simulations are presented. All papers were chosen from presentations given at the seventh Teraflop Workshop, held in November 2007 at Tohoku University, Japan; the eighth Teraflop Workshop, held in April 2008 at the Höchstleistungsrechenzentrum Stuttgart (HLRS), Germany; and at the Japan Atomic Energy Agency in April 2008.